DETERMINANTS OF FOOD INSECURITY AMONG FARMING HOUSEHOLDS IN KATSINA STATE, NORTH WESTERN, NIGERIA: AN ORDINAL LOGIT REGRESSION APPROACH - Ibrahim, Hussaini Yusuf; Adeola, Segun Solomon; Ibrahim, Hassan Ishaq (Journal of Agricultural Sciences (Belgrade), 2016)
The study identified the determinants of food insecurity among farming households in Katsina State, North-western Nigeria. A cross sectional sample survey design was used to select a total of 150 small holder farmers from 15 communities across 10 Local Government Areas of the state. A structured questionnaire, Focus Group Discussion and Key Informant Interview were used for data collection. The coping strategy index was used to determine the food security status of the household and the ordered logit regression was used to identify the determinant of food insecurity among the households. Majority (73%) were found to be food insecure. In terms of food insecurity status, 44% less of the respondents were food insecure, while 17% and 12% were moderately food insecure and severely food insecure respectively. Eating less preferred meal, purchasing food on credit and reducing the quantity of food consumed were the major coping strategies adopted by the food insecure households. The result of the ordered logit model shows that the total quantity of cereal saved, number of income sources and dependency ratio, were significant for both the moderately and severely food insecure groups at (p<0.05) while access to credit was also significant for the two groups but at (p<0.01). The output of other crops was significant at (p=0.10) but only for the severely food insecure group. The study concluded that food insecurity is high in the study area and therefore recommended that the farming households be provided with opportunities to diversify their livelihood activities.